2020
DOI: 10.1007/s00246-020-02307-0
|View full text |Cite
|
Sign up to set email alerts
|

New Screening Tool for Aortic Root Dilation in Children with Marfan Syndrome and Marfan-Like Disorders

Abstract: One of the roles of a pediatric cardiologist who suspects or diagnoses a genetically determined connective tissue disease (e.g., Marfan, Ehlers-Danlos, and Loeys-Dietz syndromes) is to assess whether the aortic root is dilated. The aortic root diameter is affected by the patient's age, sex, and body surface area. Therefore, the aortic root diameter needs to be determined and expressed as a z-score. Calculation of the z-score is time-consuming and problematic if used infrequently. This study aimed to introduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Recently, a new screening tool was reported, but only for relatively tall patients with connective tissue disease (e.g. Marfan) (Wozniak‐Mielczarek et al, 2020 ). A tool for patients with TS and short stature has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new screening tool was reported, but only for relatively tall patients with connective tissue disease (e.g. Marfan) (Wozniak‐Mielczarek et al, 2020 ). A tool for patients with TS and short stature has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, this is why thin or obese patients may be mistakenly classified if z-score formulas including body surface area are applied. A recent study showed that the aortic root ratio, which is a simple ratio of the aortic root diameter to a patient's height, does not require access to any nomograms or online zscore calculators [3]. This tool allows for rapid and precise assessment of whether the aortic root is dilated.…”
mentioning
confidence: 99%